Attracting Private Participation and Financing in the Power Sector in Sub-Saharan Africa : Findings from a Survey of Investors and Financiers - Probst, Benedict; Holcroft, Richard; Huenteler, Joern; Balabanyan, Ani; Tipping, Andrew; Robinson, Peter (World Bank, Washington, DC, 2020)
Private financing and private participation in service delivery will be required if Sub-Saharan Africa is to achieve affordable, reliable, sustainable, and modern energy for all by 2030. To find out how to elicit private interest in power sector investments in the region, we surveyed 51 private investors and financiers. The results indicate that investors perceive three segments of the market—power generation, off-grid electrification, and mini-grids—as ready for private solutions. The results provide insights for governments and development partners.